Liquid-phase catalytic growth of graphene - Vincent Teng (Journal of Materials Chemistry C, 2021)
Ability to mass produce graphene at low cost is of paramount importance in bringing graphene based technologies into market. Here we report a facile liquid-phase catalytic growth of graphene suitable for mass production. Iodine tincture is used to catalyze graphene quantum dots to form graphene films at room temperature. Such method has many advantages, such as environment friendly, high yield, low cost and wide choice of substrates. Furthermore, bandgap of the graphene films is tunable by post-annealing. A photodetector based on the graphene films was developed and could response to a broad wavelength between 365 and 1200 nm. It exhibited detectivity and responsivity of up to 1.1 x 1013 cmHz1/2W-1 and 81.3 mAW-1, respectively. Hence, the graphene films demonstrated significant applications in the field of optoelectronics. Interestingly, surface of the graphene film prepared by this method has wrinkles that can also be explored for energy storage applications.